ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT INFLASI DI INDONESIA TAHUN 2015-2019 - Aditya Dwi Ananta (2022)
Inflation certainly has an influence on Indonesia's economic conditions, especially monetary conditions. There needs to be a role from all components in keeping inflation at the desired level, including at this time which has entered the era of low inflation. The purpose of this paper was to determine the effect of interest rates, exchange rates, foreign exchange reserves and the money supply on the inflation rate in Indonesia. The object of this research is Indonesia with a sample of 2015-2019 on a monthly basis. Multiple linear regression was used as an analytical technique with the OLS (Ordinary Least Square) method. Significance tests consisting of statistical tests, F tests and coefficients of determination (R2) were also carried out. To meet the feasibility, the authors also carried out classical assumption tests in this study. This study found that money supply had a significant negative effect, while foreign exchange reserves, exchange rates, and interest rates had a significant positive effect with the most influential variable being the interest rate.